KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION (AIR) - Utami Wijaya, Tri Ullandari; Destiniar, Destiniar; Mulbasari, Anggria Septiani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— The purpose of this research is to know that the learning model of Auditory Intellectually Repetition (AIR) can improve students' mathematical concept comprehension ability. Mathematics is very necessary to be given to students ranging from elementary to college level to equip learners with the ability to understand mathematical concepts. In general, mathematics learning in Indonesia is still using the traditional approach so that the lesson of mathematics less meaningful. Based on the above problems it is necessary to have a model of learning that is considered appropriate to overcome the problem is the learning model of Auditory Intellectually Repetition (AIR) which is a learning model that emphasizes student learning activities in which students are actively building their own personal and group knowledge by integrating three aspects 1) Auditory (2) Intellectually (3) Repetition. Therefore, the learning model of Auditory Intellectually Repetition (AIR) can improve students' mathematical concept. Keywords— understanding of mathematical concepts, learning model of Auditory Intellectually Repetition (AIR). Abstrak— Tujuan penelitian ini untuk mengetahui bahwa model pembelajaran Auditory Intellectually Repetition (AIR) dapat meningkatkan kemampuan pemahaman konsep matematis siswa. Matematika sangatlah perlu diberikan kepada peserta didik mulai dari tingkat dasar sampai perguruan tinggi untuk membekali peserta didik dengan kemampuan pemahaman konsep matematis. Secara umum pembelajaran matematika di Indonesia masih menggunakan pendekatan tradisional sehingga pembelajaran matematika kurang bermakna. Berdasarkan permasalahan di atas maka diperlukan sebuah model pembelajaran yang dipandang tepat untuk mengatasi permasalahan tersebut yaitu model pembelajaran Auditory Intellectually Repetition (AIR) yakni model pembelajaran yang menekankan pada kegiatan belajar siswa dimana siswa secara aktif membangun sendiri pengetahuan secara pribadi maupun kelompok dengan mengintegrasikan tiga aspek (1) Auditory (2) Intellectually (3) Repetition. Maka dari itu model pembelajaran Auditory Intellectually Repetition (AIR) dapat meningkatkan kemampuan pemahaman konsep matematis siswa. Kata Kunci— Pemahaman Konsep Matematis, Model Pembelajaran Auditory Intellectually Repetition (AIR).